Cresp®: transforming the landscape of chemotherapy-induced anemia - a comprehensive retrospective real-world analysis in 523 Indian patients - Chandrakanth, MV; Agarwala, Vivek; Sopory, Pranav; Nayak, Himadri; Parikh, Purvish M.; Roy, Minakshi; De, Rajib; Narayan, Pradeep; Barai, Anjuli Tuladhar; Mandal, Kaustav; Basu, Moinak; Kumar, Subhabrata; et al. (Frontiers in Oncology, 2025)
IntroductionAnemia, a frequently encountered issue among cancer patients undergoing chemotherapy, is regrettably underappreciated despite its prevalence and profound impact on their well-being. Chemotherapy-induced anemia (CIA) diminishes the quality of life, causing fatigue, breathlessness, and a decline in the performance status. However, correcting anemia can lead to notable improvements in these parameters. Notably, darbepoetin alpha (DA) has shown efficacy in addressing anemia in this context. This real-world study aims to evaluate the efficacy of DA in the treatment of CIA among Indian cancer patients.MethodsThis single-center retrospective study assessed the effectiveness of DA in treating CIA among advanced/metastatic solid tumor patients on palliative myelosuppressive therapy. The study measured the change in hemoglobin levels after DA administration as the primary outcome, with secondary outcomes including impact on blood transfusion dependence, changes in anemia-related symptoms, and occurrence of adverse events.ResultsA total of 523 patients, with a median age of 55, were included in the study. Patients were categorized based on cancer site, type of chemotherapy, response to therapy, and DA doses. A significant mean increase of 2.28 gm/dl in hemoglobin (Hb) levels from baseline to post-DA administration was observed (8.56±0.45 to 10.84±0.92; 26.6%; P<.001). Each sub-group revealed a significant enhancement of mean hemoglobin from baseline to the end of treatment. Significant improvements were noted from baseline in fatigue, and dyspnea. Adverse drug reactions included hypertension (5.4%), deep vein thrombosis (2.9%), and arrhythmias (0.8%).DiscussionDA demonstrates impressive efficacy and safety in managing CIA, leading to substantial improvements in mean hemoglobin levels in palliative setting. This has the potential to reduce the need for blood transfusions and enhance the quality of life for patients.